SHELL AND TUBE HEAT EXCHANGER DESIGN FOR NANO ZEOLITE PRODUCTION PROCESS - Nedya Tresna Dwi Hidayah; Asep Bayu Dani Nandiyanto (Universitas Komputer Indonesia, 2021)
Heat exchangers are often found in the chemical process industry, but of all types of heat exchangers, the Shell and Tube Heat Exchanger (STHE) is the most commonly used. The design of heat exchangers has also been done a lot because it can reduce production costs. Therefore, this study purpose to design a tube and shell type heat exchanger for applications in producing nano zeolite. The TEMA standard is used as a reference for data collection regarding equipment specifications and dimensions. The parameters are calculated using basic Microsoft Office applications. Shell and Tube type heat exchanger (one pass) with 43 pcs of tubes has been successfully designed. The effectiveness of the heat exchanger reaches 80.02% so it is hoped that this research can be used as a reference in designing a heat exchanger with a better design.